STEM-Based E-Module Integrated Local Wisdom of Rice Stem Fertilizers on Students' Critical and Creative Thinking - Prima Aswirna; Duski Samad; Indri Saputri Devi; Reza Fahmi; Raudhatul Jannah (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
Several studies have acknowledged that using E-Modules can support the thinking and creative abilities of students to be able to learn independently and can also repeat lessons independently whenever students want. The e-module provided also contains about the sustainability of the Minangkabau custom that almost no one plays the traditional instrument, namely the rice stalk pupuik. Where is the rice stem fertilizer originating from the Payukumbuh, Lima Puluh Kota, West Sumatra. This one musical instrument is a musical instrument that has many characteristics in playing it, which has many meanings for each playing technique. This rice stem pupuik musical instrument was explained in the material of mechanical waves and sound waves from class 12 material. The game technique owned by the rice stem pupuik or the shrill sound emitted by the rice stem pupuik, was explained in learning about sound waves. From this, students will be made to think critically and creatively in finding out about the lessons of mechanical waves and sound waves which are owned by the rice stem pupuik musical instrument. The products provided in this study are very different from the E-Modules that have been made by previous researchers, namely the E-modules integrated with local wisdom of rice stem fertilizers originating from West Sumatra.